Foods For People With Kidney Diseases: Fundamental Guidelines & Choice - Rahman, Md Mahfuzar; Mahmood, Nazneen; Rahman, Md Atiqur; Sajani, Tabassum Tahmin; Alo, Kamrunnahar (Anwer Khan Modern Medical College Journal, 2017)
Chronic Kidney Disease (CKD) leads to increased cardiovascular mortality and a loss of disabilityadjusted life years. In addition lack of data / information in most low- and middle-income countries made it difficult to ascertain the true burden. Moreover, high incidence and prevalence of CKD is being driven by regional and global increase in the prevalence of Diabetes Mellitus (DM), hypertension, obesity and aging in particular. Community surveys indicate people with end-stage kidney disease are only the tip of "CKD iceberg." Therefore, preventive strategies of CKD must involve educating the population creating public awareness with early detection of CKD. The paper highlights categories of healthy foods for the people with kidney diseases for one's better choice and alternatives in choosing one's meal plan. Therefore, to deal with CKD emphasis should be given on people's awareness about fundamental guidelines and choice of available foods in order to prepare a kidney friendly diet towards better and prolong life. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 56-59